2004
DOI: 10.1108/13522750410540218
|View full text |Cite
|
Sign up to set email alerts
|

The nature of networking in small firms

Abstract: For some time, researchers at the marketing/entrepreneurship interface have employed the concepts of networks and networking as a means of exploring how entrepreneurs "do business". More recently, attempts have been made to show how the process of networking contributes to small firm marketing. The overall research study on which this paper is based aimed to show how networking contributes to marketing. This paper focuses on a specific objective of the overall research study, namely an understanding of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 47 publications
0
86
1
2
Order By: Relevance
“…Networking in SMEs varies in different dimensions that could be classified into (1) level of networking, (2) strength of network ties, and (3) networking proactivity (O'Donnell, 2004) on the continuum. The level of networking refers to the range of the network and it should be positively connected to the companies' ownership (Birley et al, 1991;Burns & Dewhurst, 1996).…”
Section: Characteristics Of Network In Smesmentioning
confidence: 99%
“…Networking in SMEs varies in different dimensions that could be classified into (1) level of networking, (2) strength of network ties, and (3) networking proactivity (O'Donnell, 2004) on the continuum. The level of networking refers to the range of the network and it should be positively connected to the companies' ownership (Birley et al, 1991;Burns & Dewhurst, 1996).…”
Section: Characteristics Of Network In Smesmentioning
confidence: 99%
“…According to O'Donnell [49], it is essential to have adequate information on the cost of similar goods and services by rival business operators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results strongly supported the hypothesis, H7 on the basis of the significant positive regression coefficient (β = 0.629 or 62.9 percent and t-value = 14.53). A large number of studies (Baker, 1990;Bouzdine and Lorgnier, 2004;Burt, 2000;Donnell, 2004;Granovetter, 1983;Jones et al, 1997;Ting et al, 2007) empirically confirmed that network structure plays an important role in sharing information which leads to improve rational ability (mitigate bounded rationality). The results of this study further strengthen the idea of Coleman (1988) who explained that dense network exchanges information among members.…”
Section: Resultsmentioning
confidence: 99%